Public Choice with Unequally Rational Individuals - Pavel Pelikan (Albert-Ludwigs-Universität Freiburg, Institut für Allgemeine Wirtschaftsforschung, Abteilung für Wirtschaftspolitik, 2007)
As governments lack the rationality-promoting selective pressures of market competition, the standard (unbounded) rationality assumption is less legitimate in Public Choice than in analysis of markets. This paper argues that many Public Choice problems require recognizing that human rationality has bounds, that these differ across individuals, and that rationality must therefore be treated as a special scarce resource, tied to individuals and used for deciding on its own uses. This complicates resource-allocation in society, which has to rely on institutionally shaped selection processes. But this also appears to be the only way to produce the long-missing analytical support to the first head of J.S. Mill's criticism of government, of which Public Choice has so far supported only the second.
Keywords: P51; H10; D60; 330; unequally bounded rationality; institutions; voting; politics-as-selection; government policies; Public Choice; Beschränkte Rationalität; Theorie